How do students’ accounts of sociology change over the course of their undergraduate degrees? - Ashwin, Paul; Abbas, Andrea; McLean, Monica (Springer, 2014)
In this article we examine how students’ accounts of the discipline of sociology change over the course of their undergraduate degrees. Based on a phenomenographic analysis of 86 interviews with 32 sociology and criminology students over the course of their undergraduate degrees, we constituted five different ways of accounting for sociology. These ranged from describing sociology as a form of personal development focused on developing the students’ opinion to describing sociology as a partial way of studying the relations between people and society. The majority of students expressed more inclusive accounts of sociology over the course of their degrees. However, some students’ accounts suggested they had become disengaged with sociology. We argue that the differences in the ways that students were disengaged were not captured by our phenomenographic categories. In conclusion, we argue that our analysis illustrates the crucial role that students’ relations to knowledge play in understanding the transformative nature of higher education.